2019
DOI: 10.1101/736629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Hurricane Michael on longleaf pine habitats in Florida

Abstract: 9The longleaf pine (Pinus palustris) ecosystem of the North American Coastal Plain (NACP) is a global 10 biodiversity hotspot. Disturbances such as tropical storms play an integral role in ecosystem maintenance in 11 these systems. However, altered disturbance regimes as a result of climate change may be outside the historical 12 threshold of tolerance. Hurricane Michael impacted the Florida panhandle as a Category 5 storm on October 13 10th, 2018. In this study, we estimate the extent of Florida longleaf habi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The spatio-temporal patterns of land disturbances are changing due to both anthropogenic and natural agents of disturbance [3]. Hurricanes are a major contributor to deforestation in states bordering the Atlantic and Gulf of Mexico regions of the southern United States [4,5], while in the western United States, forest fires, which are the second largest cause of disturbances, have increased since the mid-1980s [6,7]. In Europe, disturbances caused by wind, bark beetles, and wildfires have also increased over the last century [8].…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal patterns of land disturbances are changing due to both anthropogenic and natural agents of disturbance [3]. Hurricanes are a major contributor to deforestation in states bordering the Atlantic and Gulf of Mexico regions of the southern United States [4,5], while in the western United States, forest fires, which are the second largest cause of disturbances, have increased since the mid-1980s [6,7]. In Europe, disturbances caused by wind, bark beetles, and wildfires have also increased over the last century [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 248 Restore plots, only two were misclassified by the tree presence model. The BA general linear model results were R 2 = 0.508, adjR 2…”
Section: Basal Area Model Resultsmentioning
confidence: 99%
“…It was the second strongest hurricane to make landfall on the continental United States, with estimated maximum sustained winds of 259 km/h, and was the first category 5 hurricane on record to make landfall in this area [1]. An early study found that the hurricane caused 88.7% tree mortality at some longleaf pine sites [2].…”
Section: Introductionmentioning
confidence: 99%
“…Additional application areas where BNs could be useful include modeling interacting disturbances such as fires and storms with critical causal cascades from post-fire debris flows (e.g., Staley et al, 2018) and extreme erosion events (e.g., O. D. Jones et al, 2014). Hurricane and storms not only have the potential to degrade habitat but could lead to dramatically altered fuel complexes (St Peter et al, 2020;Zampieri et al, 2020) and may have long-term benefits to habitat through succession or renewal. Interacting disturbances such as beetle impacts and fire are another opportunity for examining ecological risks and management opportunities (Moriarty et al, 2019;Page et al, 2013).…”
Section: Discussionmentioning
confidence: 99%